Development of a defined minimal culture medium for Prevotella copri DSM 18205 - Nieto Esteve,Anna (2020)
The human gut microbiota is involved in the host’s health and disease. There has been growing interest in the next generation probiotic candidate Prevotella copri, which plays a beneficial role in glucose metabolism. It is a Gram-negative obligate anaerobe that was first isolated from human faeces and which is present in plant-based fermented foods as well as in human breast milk. The aim of this project was to develop a minimal culture medium free from animal-derived ingredients, within the framework of potentially developing a fermented food product that contains P. copri in collaboration with Aventure AB. The first phase of the project consisted of assessing the optimal pH condition as well as the efficacy of commercial horse serum in the complex medium PYG (Peptone Yeast Glucose) for growing P. copri. The second phase of the project involved the formulation of the DMMG (Defined Minimal Medium Glucose) as well as the evaluation of plant-derived haemoglobin (BvHb) as a substitute of commercial hemin in the culture medium. The optimal pH for growing P. copri was 7.2, and the addition of horse serum was not indispensable for its successful growth in PYG. The DMMG was developed based on culture media previously formulated for Bacteroides fragilis, which rendered an acceptable biomass and succinic acid production. Moreover, the omission of hemin favoured the growth of P. copri in DMMG, which is inconsistent with previous studies. This finding suggests that more research is needed in order to elucidate the role of hemin in the cultivation of P. copri as well as to improve the formulation of the DMMG to enhance the biomass production.
Keywords: Prevotella copri; probiotics; fermentation; hemin; biotechnology; bioteknik